School Violence and Teacher Professional Engagement: A Cross-National Study - Yang, Youcai; Qin, Lixia; Ning, Ling (Frontiers in Psychology, 2021)
School violence research has mainly focused on the impact on students. Very few studies, even fewer from a cross-cultural perspective, have examined the relationships between school violence and teacher professional engagement, and the role played by teacher self-efficacy and school climate related factors. The present study utilizes a SEM research methodology to analyze the 2013 TALIS data. The purpose is to understand and compare the relationships in four different cultural contexts: the U.S., England, South Korea, and Mexico. Results indicate, on average, the significant and negative impacts of school violence on teacher professional engagement are partly mediated by teacher self-efficacy. The negativity of school violence is significantly alleviated by enhancing participation among school stakeholders and improving teacher-student relationship. The relationships among the factors apply across all four cultural systems though the effects of factors and variables vary to a degree. The paper also discusses other relevance and differences as well as implications.